Dramaturgi Master of Ceremony Wedding Di Kota Bandung - Muhamad Sinki Alwin; dadan Mulyana (Bandung Conference Series: Public Relations, 2022)
Abstact. Life according to dramaturgy theory is like a theater, a social interaction similar to a drama show, which presents a role. In playing the role of using verbal language and non-verbal behavior and wearing certain attributes. Social life is divided into the front region (front region), which refers to social events in which the individual is stylish in displaying his role and the (back region)n. In this study, who were taken as informant is Dody Danudiwiryo or Dody 3d as a Master of Ceremon Wedding in Bandung City. This research is limited to studying and analyzing the front stage and back stage in dramaturgy theory to determine the impression management that is formed. This type of research uses qualitative research with a dramaturgy approach. as for data collection technique that is interview, observation, documentation and literature studyBased on the results of this study, there were informants. Impression management or impression management is the key to the results of the front stage and back stage processes. The result is author find a different side of Front Stage and Back Stage. Abstrak. Kehidupan menurut teori dramaturgi adalah ibarat teather, interaksi sosial yang mirip pertunjukan drama, yang menampilkan peran. Dalam memainkan peran menggunakan bahasa verbal dan perilaku non verbal dan mengenakan atribut tertentu. kehidupan sosial dibagi menjadi wilayah depan” (front region) yang merujuk peristiwa sosial bahwa individu bergaya menampilkan perannya dan wilayah belakang (back region). Dalam penelitian ini, yang diambil sebagai informan adalah Dody Danudiwiryo atau Dody 3D sebagai MC Wedding di Kota Bandung. Penelitian ini dibatasi untuk mengkaji dan menganalisis panggung depan dan panggung belakang pada teori dramaturgi untuk mengetahu impression management yang terbentuk. Tipe penelitian ini memakai penelitian kualitatif dengan pendekatan dramaturgi. Adapun teknik pengumpulan data yitu dengan wawancara, observasi, dokumentasi dan studi kepustakaan. Berdasarkan hasil penelitian ini yang dijadikan informan ada Impression managemen atau pengelolaan kesan adalah merupakan kunci dari hasil proses panggung depan (Front Stage) dan Panggung belakang (Back Stage). Hasil dari penelitian ini peneliti menemukan perbedaan antara panggung depan dan panggung belakang pada salah satu Mc Wedding Dody 3D.